Controller reduction by balanced approach with guaranteed closed-loop performance - Kumar D.; Tiwari J.P.; Nagar S.K. (My University, 2025)
This paper addresses an algorithmic approach for controller reduction problem using balanced singular perturbation approximation (BSPA) technique for un-weighted cases. The controller design methods generally lead to a controller of order comparable to plant and sometimes unstable controllers. For reduction of such controllers, a controller decomposition algorithm in conjunction with BSPA technique is presented. It is shown by numerical examples that reduced order controller by balanced truncation fails for some cases to stabilize the closed-loop system whereas resulting closed-loop system with reduced order controller using BSPA is guaranteed to preserve the closed-loop system stability and H∞ performance. Copyright © 2012 Inderscience Enterprises Ltd.